Fellows letter, - Fellows, E. B.
One letter from E. B. Fellows of Oregon City, Oregon to his brother and sister. The letter is actually signed E. B. and E. A. Fellows. It talks about the trip and general family matters. The letter, dated September 11, 1864, talks about the Civil War ("bulley for Sherman and Hurraw for Grant<U+2026>"). Otherwise, the letter talks about health and general family issues.